2020
DOI: 10.3389/fpsyg.2020.575929
|View full text |Cite
|
Sign up to set email alerts
|

Beat Gestures for Comprehension and Recall: Differential Effects of Language Learners and Native Listeners

Abstract: Previous work has shown how native listeners benefit from observing iconic gestures during speech comprehension tasks of both degraded and non-degraded speech. By contrast, effects of the use of gestures in non-native listener populations are less clear and studies have mostly involved iconic gestures. The current study aims to complement these findings by testing the potential beneficial effects of beat gestures (non-referential gestures which are often used for information-and discourse marking) on language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
3
7
0
Order By: Relevance
“…Our analyses of beat gestures revealed that bilinguals also used more beat gestures than monolinguals. This is consistent with the idea that bilinguals increased their gesture frequency because of higher cognitive demands, in particular given that beat gestures have been suggested to boost attention and facilitate semantic integration (e.g., Biau & Soto-Faraco, 2013;Dimitrova, Chu, Wang, Özyürek, & Hagoort, 2016; but also see discussion by Rohrer, Delais-Roussarie, & Prieto, 2020). In addition, visual inspection of the data suggests that the increased rate of beat gestures in bilingual caregivers is most pronounced in the adult-directed setting.…”
Section: Discussionsupporting
confidence: 85%
“…Our analyses of beat gestures revealed that bilinguals also used more beat gestures than monolinguals. This is consistent with the idea that bilinguals increased their gesture frequency because of higher cognitive demands, in particular given that beat gestures have been suggested to boost attention and facilitate semantic integration (e.g., Biau & Soto-Faraco, 2013;Dimitrova, Chu, Wang, Özyürek, & Hagoort, 2016; but also see discussion by Rohrer, Delais-Roussarie, & Prieto, 2020). In addition, visual inspection of the data suggests that the increased rate of beat gestures in bilingual caregivers is most pronounced in the adult-directed setting.…”
Section: Discussionsupporting
confidence: 85%
“…Even though the empirical evidence of the value of non-referential gestures is not yet as strong as the evidence in favor of referential gestures, it is clear that there are sufficient grounds to claim that non-referential gestures play an important role in boosting children's learning and language development. It is of interest to note that the mixed findings obtained in the developmental literature resemble the contradictory patterns reported by studies assessing the role of nonreferential gestures in adult speech processing (see [85] for a review). While some research has shown that non-referential gestures positively affect adults' ability to recall information [20,86,87], this has not been true of other studies [77,79,88] (see also [85]).…”
Section: Discussionmentioning
confidence: 90%
“…It is of interest to note that the mixed findings obtained in the developmental literature resemble the contradictory patterns reported by studies assessing the role of nonreferential gestures in adult speech processing (see [85] for a review). While some research has shown that non-referential gestures positively affect adults' ability to recall information [20,86,87], this has not been true of other studies [77,79,88] (see also [85]). According to [85], a potential reason for the lack of the beneficial effect of non-referential gestures reported in some studies could be related to the stimuli used, as positive results have generally been shown when non-referential gestures are used in pragmatically natural and restricted contexts, such as for marking contrastively focused information.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies failed to find the same N400 effects of beat gestures [43,44]. However, these studies used artificial beat gestures (one single stroke per sentence), which are different from naturally occurring beat gestures (see also [74]). Alternatively, the lack of any meaningful gestures in previous studies could have discouraged listeners from paying attention to gestures.…”
Section: Discussionmentioning
confidence: 99%